The Urgency of Children Education in Preventing Mass Ignorance in Indonesia - Mansir, Firman (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to explain the importance of children’s education in preventing ignorance. This study used a qualitative approach. As for the subjects of this research are Indonesian children who are inÂ MuhammadiyahÂ YogyakartaÂ school. This research was conducted online considering theÂ Covid-19 pandemic is still engulfing Indonesia, so face-to-face via zoom and direct interviews were conducted. Â The data analysis technique used was descriptive qualitative. Â The results show that early childhood education is very important to prevent stupidity because children need to be given insight and understanding about the world of children. So that they are able to face their lives appropriately and are not affected by the currents of social life. Thus, this study showed that educational failures could result in ignorance for Indonesian children. The emergence of mass ignorance, of course, did not happen suddenly, but there was a cause to it. Experts stated that the mass ignorance is due to the lack of education, the lack of knowledge about science and technology and the laziness of some children. Therefore, the mass ignorance in children’s education should be erased by giving necessary education to advance their thinking. Also, children’s education must be positioned as the target of all educational endeavors because education aims to inculcate all aspects and values of a good life to prevent and reduce mass ignorance in Indonesia.